2014
DOI: 10.1063/1.4901576
|View full text |Cite
|
Sign up to set email alerts
|

Landau damping in a multi-component dusty plasma

Abstract: Articles you may be interested inDust negative ion acoustic shock waves in a dusty multi-ion plasma with positive dust charging current Attractive wake field formation due to an array of dipolar projectiles in a multi-component dusty plasma Phys. Plasmas 10, 941 (2003);Effect of the dust size distribution on the landau damping and the wave frequency is studied in the present paper. It is found that wave frequency increases as either the difference between the largest and the smallest dust size increases or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…When dissipation in the system is large it can overcome the role of dispersion, case when the balance between nonlinearity and dissipation can generate shock waves [30,31,237]. A very effective method for studying these phenomena is the particle-in-cell (PIC) simulation [363,364,365,366].…”
Section: Regions Of Single Particle Confinementmentioning
confidence: 99%
See 1 more Smart Citation
“…When dissipation in the system is large it can overcome the role of dispersion, case when the balance between nonlinearity and dissipation can generate shock waves [30,31,237]. A very effective method for studying these phenomena is the particle-in-cell (PIC) simulation [363,364,365,366].…”
Section: Regions Of Single Particle Confinementmentioning
confidence: 99%
“…We assume the particles are cold and their flow velocity is zero at an initial The time evolution of such a system of charged particles is studied using the particle-in-cell (PIC) method, developed and widely used to investigate the dynamics of a collisionless plasma [363,364,365,366]. By using the PIC method the material medium is represented by a set of particles that move under the influence of an electromagnetic field, which in turn is determined by the particle distributions and their associated electric currents.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…On the other hand, with the main collision features being presented in the long particle chain during the theoretical simulation, a short structure with fewer particles can be applied to the practical test. The material parameters of these particles are listed in Table 1, as well as u LI = u RI = 1 and ε = 0.002 are applied [58][59][60][61]. In order to show the overlap between adjacent particles which result in the no separation during the wave propagation, the prestress is used to the whole periodic system.…”
Section: Numerical Calculations and Discussionmentioning
confidence: 99%
“…Based on wave-particle response interactions used to modify the shape of the solution a detailed study was proposed, as it was observed, these interactions in the plasma lead to the acceleration of charged particles as a result of the transfer of wave energy to these particles 19 . Recently, experimental results have predicted the formation of acoustic ion shock waves due to the dissipation caused by Landau damping 20 . Arnab Barman and A. P. Misra investigated the effect of Landau damping of two types of ions (positive and negative) on electrostatic solitary waves in dusty multicomponent plasma 21 .…”
Section: Introductionmentioning
confidence: 99%